Changes in gastric mucosa after vagotomy and gastrojejunostomy for duodenal ulcer. Issue 6403 (12th November 1983) - Watt, P C; Sloan, J M; Kennedy, T L
Abstract : Gastric mucosa was studied histologically in 141 patients. Eighty two had undergone vagotomy and gastrojejunostomy between 15 and 25 years previously for duodenal ulcer, and 59 control patients had a long history (minimum 15 years) of duodenal ulcer treated medically. No carcinoma was found in either group. Two patients with severe dysplasia and 13 patients with moderate dysplasia were found in the study group, compared with none in the control group (p less than 0.01). Intestinal metaplasia was seen in 44 (53%) of the study group and 16 (27%) of the control group (p less than 0.01). Atrophy and gastritis were more severe (p less than 0.01 for atrophy; p = 0.05 for gastritis) in the study group. Gastric mucosal changes were more severe after surgical treatment for duodenal ulcer than after medical treatment, and possibly a high incidence of gastric carcinoma may occur 25 years after vagotomy and gastrojejunostomy.